P067 Why don't people with genito-urinary symptoms go to sexual health clinics? A mixed methods study about meanings of symptoms and care-seeking using the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3). (30th June 2016) - Mapp, Fiona; Hickson, Ford; Mercer, Cath; Wellings, Kaye
Abstract : Background/introduction: There are both individual and public health benefits in people responding to genito-urinary symptoms effectively. Sexual health clinics are best equipped for managing symptoms but not everyone with symptoms chooses to attend. Aim(s)/objectives: To examine the prevalence and meanings of genito-urinary symptoms and the impact on non-attendance at sexual health clinics among people in Britain. Methods: An explanatory sequential mixed methods study design was used to estimate symptom and clinic non-attendance prevalences using data from 8, 947 sexually-experienced women and men aged 16–44 years who participated in Britain's third National Survey of Sexual Attitudes and Lifestyles (Natsal-3). We conducted follow-up semi-structured interviews with Natsal-3 participants (n = 27) who reported current or recent symptoms and had never attended a clinic, in order to explore STI perceptions, symptom meanings and care-seeking behaviour. Results: Prevalence of experiencing symptom(s) in the last month was 21.6% (95% CI 20.4–22.9%) among women and 5.6% (95% CI 4.9–6.6%) among men, of whom 86.3% (95% CI 84.2–88.1) reported not having attended a sexual health clinic in the past year. Bodily changes were not always viewed as symptoms and perceived potential causes were diverse, causing strong emotional responses. Individuals normalised, concealed and/or distanced their experiences from STIs. GPs were the preferred service provider although not all participants perceived a need for care. Discussion/conclusion: Symptoms are more commonly reported by women although both women and men may benefit from interventions targeting symptom normalisation and concealment. Good links between services will facilitate efficient and appropriate care-seeking and service delivery.